Design of Internet of Things (IoT)-Based Boarding Room Security System Using Wemos D1 Mini and Door Sensor, and Integration of Notification Via Telegram - Ikhsan, Muhammad Khairul (Al'Adzkiya, 2023)
The advancement of Internet of Things (IoT) technology presents significant opportunities to enhance security in various aspects of daily life, including in residential environments such as boarding rooms. This research aims to design a boarding room security system based on IoT that uses the Wemos D1 Mini as the main controller and a door sensor to detect entry and exit access at the room‟s door. The system operates by detecting changes in the door's status and sending real-time notifications via the Telegram application when unexpected access occurs. When the door opens, the door sensor sends data to the Wemos D1 Mini, which then processes the information and delivers a notification to the user through Telegram. Telegram was chosen as the notification medium due to its high accessibility and ability to support instant messaging across various devices. Testing shows that the system has a high level of accuracy in detecting door activity and can send notifications in less than one second after access occurs. This IoT-based security system is thus expected to be an effective and affordable solution to enhance boarding room security and provide peace of mind to resident.